FUNDAMENTALS OF TECHNOLOIFICATION OF THE PROCESS OF SHAPING STUDENTS AS SOCIALLY ACTIVE INDIVIDUALS - Alqarov Idris Shodievich. (Scholar Express Journal, 2024)
The purpose of this article is to organize the process of technologizing the formation of students as socially active individuals. To implement this goal, the mechanism of applying modern educational technologies to the study of the components of the model of forming students as socially active persons consists in creating a system of technology development, determining the stages of the process of formation of knowledge and skills, forming a computer educational communication program
Keywords: education; upbringing; perfect person